A Newly Discovered Fragment of William Caxton's Ordinale. (18th December 2020) - Delbecque, Erika
Abstract: This note discusses the find of a hitherto unknown leaf from William Caxton's Ordinale seu Pica ad usum Sarum at the University of Reading Special Collections Service. It provides a bibliographical analysis of the leaf and explores its provenance. It concludes with a semi-diplomatic transcription, with reference to BL Add. MS 25456, the only known surviving manuscript copy of the text.